Capillary Electrophoresis in Forensic Chemistry - Tagliaro, F.; Pascali, J.; Lewis, Simon (Academic Press, 2013)
The separation and quantification of chemical substances in a wide variety of complex matrices is a significant analytical challenge to the forensic chemist. Capillary electrophoresis (CE) is attractive to the forensic chemist as it has the potential to provide exceptional separating power in combination with rapid analysis times and high mass sensitivities. It is also economical of both reagents and sample. Owing to the variety of separation modes possible (electrophoretic, electrokinetic, chromatography-like, etc.) and the detection systems available (UV–visible absorbance, luminescence, and mass spectrometry are all available commercially), it is applicable to the determination of a wide variety of chemical substances including inorganic ions, small organic molecules, chiral compounds, macromolecules, and intact viruses and cells. This article provides an overview of the application of CE to forensic chemical analysis, illustrated with recent examples.